Which stereotest do you use? A survey research study in the British Isles, the United States and Canada - Vancleef, K; Read, J (British and Irish Orthoptics Society, 2019)
A wide range of stereotests are available to measure stereopsis. Because each test has its own advantages and disadvantages, opinions differ on which is the preferred test to use in clinical practice. We conducted surveys comparing the use of stereotests in the British Isles and in the United States and Canada. Two online surveys were developed following consultation with eye care professionals, one for each geographical area. Both surveys included two questions on the frequency of use of different stereotests, two questions on best practice stereotests, and two questions on the usefulness of stereotests. Researchers made distinctions between appointments with children below or above 6 years old for respondents from the British Isles and below or above 5 years old for respondents from the Unites Stated and Canada. The surveys were distributed through professional organisations. We found Frisby to be the most used stereotest on the British Isles for both age groups. In the US and Canada, Titmus and Randot stereotest are more frequently used. Respondents consider these tests as the best practice stereotests. Eye care professionals agree stereotests are useful in the diagnosis and treatment decision making and even more so in obtaining an accurate measure of stereoacuity, especially with older children.